2016
DOI: 10.1111/acer.12976
|View full text |Cite
|
Sign up to set email alerts
|

PPAR Agonists: I. Role of Receptor Subunits in Alcohol Consumption in Male and Female Mice

Abstract: Background Several peroxisome proliferator-activated receptor (PPAR) agonists reduce voluntary alcohol consumption in rodent models, and evidence suggests that PPARα and γ subunits play an important role in this effect. To define the subunit dependence of this action, we tested selective PPARα and α/γ agonists and antagonists in addition to null mutant mice lacking PPARα. Methods The effects of fenofibrate (PPARα agonist) and tesaglitazar (PPARα/γ agonist) on continuous and intermittent two-bottle choice dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 27 publications
2
37
1
1
Order By: Relevance
“…For example, Ferguson et al showed pretreatment with fenofibrate (150mg/kg/8 days, PO) decreased EtOH (15%) consumption in mice using a continuous access two-bottle choice drinking procedure (Ferguson et al, 2014). A more recent study showed similar results following fenofibrate (100 and 150mg/kg, PO) administration in mice using continuous and intermittent 2-bottle choice EtOH (15%) drinking tests (Blednov et al 2016a). In that same study, fenofibrate administration in mice lacking PPARα did not alter EtOH consumption but did in wild-type mice thus showing specificity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, Ferguson et al showed pretreatment with fenofibrate (150mg/kg/8 days, PO) decreased EtOH (15%) consumption in mice using a continuous access two-bottle choice drinking procedure (Ferguson et al, 2014). A more recent study showed similar results following fenofibrate (100 and 150mg/kg, PO) administration in mice using continuous and intermittent 2-bottle choice EtOH (15%) drinking tests (Blednov et al 2016a). In that same study, fenofibrate administration in mice lacking PPARα did not alter EtOH consumption but did in wild-type mice thus showing specificity.…”
Section: Discussionmentioning
confidence: 66%
“…Recent studies have shown the PPARα agonist fenofibrate (a pro-drug for fibrinic acid) decreases voluntary EtOH consumption in mice (Blednov et al, 2016; Ferguson et al, 2014) and rats (Karahanian et al, 2014). Similarly, gemfibrozil, a PPARα partial agonist, also decreases voluntary EtOH intake in rats (Barson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fenofibrate, tesaglitazar, and pioglitazone also significantly altered multiple behaviors associated with alcohol consumption. Blednov et al (2016a) demonstrated decreased novelty-induced locomotion, reduced ethanol-induced loss of righting reflex, reduced ethanol withdrawal symptoms, and enhanced ethanol metabolism with some sex differences. Neither fenofibrate nor tesaglitazar reduced ethanol-induced CPP.…”
Section: New Horizonsmentioning
confidence: 99%
“…Pioglitazone reduced operant responses for ethanol, but not saccharin, reduced yohimbine-induced (but not cue-induced) ethanol reinstatement, and reduced ethanol withdrawal scores independent of PPARα activation (Stopponi et al, 2011). Although the ability of PPAR agonists to reduce drinking appears to be dependent on presence of the α subunit, the γ subunit may be critical for enhancing the effects of PPARα agonists on alcohol-related behaviors (Stopponi et al, 2011; Blednov et al, 2016a; 2016b). …”
Section: New Horizonsmentioning
confidence: 99%
“…Several FDA-approved drugs with anti-inflammatory and immune inhibitory effects regulate alcohol responses in animal models, lending support that some of these could potentially be repurposed to treat AUD. For example, the peroxisome proliferator-activated receptor (PPAR) agonists, fenofibrate and tesaglitizar, reduced drinking in a PPARα-dependent manner (Blednov, Black, Benavidez, Stamatakis, & Harris, 2016), altered expression of immune genes in the liver, and altered neuronal gene expression in mouse brain (Ferguson, Most, Blednov, & Harris, 2014). There is overlapping evidence in mice and humans for specific PPAR genes in alcohol consumption and dependence (Blednov, Benavidez, Black, Ferguson, et al, 2015).…”
Section: Medication Developmentmentioning
confidence: 99%